The refugees and health crisis: migration policy management and government response to Afghan migrants - Kalsoom B. Sumra; Muhammad Mumtaz; Naqib Ullah Khan; Helen Huifen Cai; Qiong Yuan (BMC Health Services Research)
Abstract Background The health crisis during the pandemic and its aftermath have caused multidimensional shifts within the economic and societal structure for refugees and other marginalized communities. Many countries have implemented programs to cater for the additional needs of underserved populations, but refugees and other migrants are usually not covered by these programs. In this context, this study attempts to explore the impact of the crisis on Afghan refugee's vulnerability and the relationship between health services, relief packages, and risk communication. Methods The proposed model is tested with 427 Afghan refugees’ families from five major cities of Pakistan. The partial least squares structural equation modelling (PLS-SEM) is used to test the vulnerability significance with the crisis and government response in facilities. Findings The research findings show that post pandemic economic crisis, the access to health services, relief packages and risk communication is directly associated with Afghan refugees’ vulnerability (β = 0.471, β = 0.501, β = 0.271 & β = 0.259). Notably the relationship between post pandemic economic crisis and Afghan refugees’ vulnerability is mediated by limited access to health services and unavailability of relief packages. Unavailability of relief packages and lack of risk communication mediates the effect of refugees’ crisis on vulnerability. Overall, the proposed model explains 63.3% of the variance in Afghan refugees’ vulnerability with government services. It indicates that Afghan refugees are unable to access relief packages, and there is insufficient communication of risk factors. The lack of government facilities is due to the harder closed-door policy of the Pakistani government which has worsened the vulnerability of Afghan refugees after the sudden victory of the Taliban in Afghanistan. Conclusions In spite of hosting Afghan refugees for the last forty years, the government of Pakistan has no clear systemized policy towards Afghans till now. The paper offers practical policy implications as there is a need for migration policy management combining flexibility and friendliness cooperation to provide government services to refugees. Government preparedness has to include refugee populations in responses to emergencies and look into the current state of new Afghan refugees’ flows, and take further extension in the continuation of migration management.